(untitled) (Al-Academy, 2016)
Find taught dimension aesthetic in the formation of post-modernism, which is one of the themes of aesthetics in the stream of postmodernism, is problematic because of the lack of provisions and fixed values reinforce the concept of beauty, and put done technical plastic in the circle of evaluation and judgment aesthetic, this research as an attempt to reveal the aesthetic concepts that can be drawn from artistic experiments in the formation of post-modernism, through the development of those concepts viable mainstream.Search contains four chapters: the first chapter includes a general approach to the research, has been showcasing the research problem and the importance of research and goal of Search: detection dimension aesthetic in the formation of post-modernism, and then installed limits search time: the period between years 1950 2009 m, and the limits of spatial in Europe and America, as was the definition of the term (the aesthetic dimension) in determining the terms. Chapter II included: Axis philosophical and theoretical framework of the research, by identifying the philosophy of beauty in postmodern thought, and the review and discussion of philosophical dialogues. While includes Chapter III: The Search through measures identify the research community sample search tool search and research methodology, and then samples were analyzed sample (5) models, have been selected intentionality way represent the research community.Chapter IV devoted to the search results, and was the most important results: the aesthetic dimension in the formation of postmodern sculpture is the concept of variable and variable (non-fixed), beauty depends on experimenting with new Technical Works. As it turns out that the aesthetic dimension of investigating the formation of postmodern sculpture through the active participation of elements of aesthetic experience: the sculptural work, the viewer, sculpture place. It turned out that to realize the beauty and sense it in the formation of postmodern sculpture, condenses by surprising and shocking achieved when people, through the continuous search for forms of strange and unconventional.